Association of aging-related genes with prognosis and immune infiltration in pancreatic adenocarcinoma - Xue, Shengbai; Ge, Weiyu; Wang, Kexuan; Mao, Tiebo; Zhang, Xiaofei; Xu, Haiyan; Wang, Yongchao; Yao, Jiayu; Li, Shumin; Yue, Ming; Ma, Jingyu; Wang, Yanling; et al. (Frontiers in Cell and Developmental Biology, 2022)
Pancreatic adenocarcinoma (PAAD) is a deadliest malignancy. Aging is described as a degeneration of physiological function, which is complexly correlated with cancer. It’s meaningful to explore the influences of aging-related genes (ARGs) on PAAD. Based on The Cancer Genome Atlas (TCGA) and Genotype-Tissue Expression (GTEx) datasets, we used univariate Cox regression analysis and acquired 8 differentially expressed ARGs with prognostic value. Two molecular subtypes were identified based on these ARGs to depict PAAD patients’ overall survival (OS) and immune microenvironments preliminarily. Cluster 1 had a poor OS as well as a worse immune microenvironment. Through Least absolute shrinkage and selection operator (LASSO) regression analysis, we constructed a seven-ARG risk signature based on TCGA dataset and verified in Gene Expression Omnibus (GEO) and International Cancer Genome Consortium (ICGC) to predict the prognoses, immune microenvironments, signal pathways, tumor mutations and drug sensitivity of PAAD patients. High-risk group possessed an unfavorable OS compared with low-risk group. We also verified the independence and clinical availability of the risk signature by Cox regression analyses and establishment of a nomogram respectively. Higher risk score was associated with several clinical factors such as higher grade and advanced tumor stage as well as lower ImmuneScore and cluster 1. The negative associations of risk score with immune, stroma and estimate scores proved the terrible immune microenvironment in high-risk group. Relationships between risk score and immune checkpoint genes expression as well as signal pathways provided several therapeutic targets. PAAD patients in low-risk group possessed lower tumor mutations as well as higher susceptibility of axitinib and vorinostat. High-risk group bore a higher TMB and cisplatin and dasatinib may be better options. We used immunohistochemistry and qPCR to confirm the expression of key ARGs with their influences on OS. In conclusion, we identified two ARGs-mediated molecular subtypes and a novel seven-ARG risk signature to predict prognoses, immune microenvironments, signal pathways, tumor mutations and drug sensitivity of PAAD patients.